Long-term oral administration of naringenin counteracts aging-related retinal degeneration via regulation of mitochondrial dynamics and autophagy - Chen, Guiping; Zeng, Ling; Yan, Feng; Liu, Jinlong; Qin, Mengqi; Wang, Feifei; Zhang, Xu (Frontiers in Pharmacology, 2022)
Aging-related retinal degeneration can manifest as decreased visual function due to damage to retinal structures and dysfunction in retinal homeostasis. Naringenin (Nar), a flavonoid, has beneficial effects in preventing cellular aging, preserving the functionality of photoreceptors, and slowing down visual function loss. However, the role and potential mechanism of Nar in the aging mouse retina require further investigation. In this study, we evaluated the effects of Nar on the aging eye using electroretinogram (ERG) and hematoxylin and eosin staining and explored its potential mechanism by western blotting. ERG showed that Nar increased the amplitude of the a- and b-waves of scotopic 3.0, 10.0, and the a-wave amplitude of photopic 3.0 in the aging mouse retina. Furthermore, administration of Nar prevented aging-induced retinal degeneration in various layers. The expression of mitochondrial fusion regulator protein mitochondrial fusion protein 2 was increased, and mitochondrial fission of dynamin-related protein 1 was decreased in aging mice treated with Nar. Furthermore, the downregulation of age-related alterations in autophagy was significantly rescued in the aging mice by treatment with Nar. Taken together, these results suggest that the oral administration of Nar improves visual function, retinal structure, mitochondrial dynamics, and autophagy in the aging mouse retinas. Hence, we conclude that Nar may be a potential dietary supplement for the prevention or treatment of aging-related retinal degeneration.